Effects of Transcranial Direct Current Stimulation on Upper Limb Muscle Strength and Endurance in Healthy Individuals: A Systematic Review and Meta-Analysis - Hu, Kun; Chen, Yu; Guo, Feng; Wang, Xin (Frontiers in Physiology, 2022)
Objective: Whether transcranial direct current stimulation (tDCS) can improve upper limb muscle strength and endurance in healthy subjects is still controversial. This article reviews the relevant literature on the use of tDCS to improveing upper limb muscle strength and endurance in healthy individuals. Methods: We systematically searched the Cochrane Library, PubMed, EMBASE, and the Web of Science until September 4, 2021Until September 4, 2021, we have systematically searched the following databases: Cochrane library, Pubmed, EMBASE, Web of Science. Randomized parallel or cross-over experimental studies on the effects of tDCS on upper limb muscle strength and endurance in healthy individuals were included. Review Manager 5.3 software was used to evaluate the methodological quality and analyze the combined effect of the included literature. Results: Twelve studies (189 participants) were included in the qualitative synthesis, and 9 studies (146 participants) were included in the meta-analysis. Compared with the control group, the tDCS intervention had no significant effect on improving upper limb muscle strength [I2=0%, 95% CI (-0.79, 0.23), p=0.98, MD=0.01]. In this analysis, tDCS had a significant heterogeneity (I2=87%) in improving upper limb muscle endurance compared with the control group. After the subgroup analysis and the sensitivity analysis, the source of heterogeneity was excluded. The final results showed that tDCS had a significant effect on improving upper limb muscle endurance [I2 = 0%, 95% CI (1.91, 4.83), p<0.00001, MD=3.37]. Conclusions: tDCS has no significant effect on improvement of upper limb muscle strength, but has a significant effect on improving upper limb endurance performance (especially on the non-dominant side).